Desa Wisata Gerbang Utama Bantul: Inovasi Kegiatan Kepariwisataan dan Umkm untuk Kemandirian Ekonomi Masyarakat Kalurahan Trimurti - Damasdino, Fian; Afif, Fuadi; sugesti, sahlit; Putri Nuraeni, Anggita Dyah; Purnama Dewi , Bulqis; Camelia, Nur Dina; Amal, M. Ikhlasul; Baharezky, Anggi Puspa; Safitri, Viya Riska (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Bantul Main Gate Tourism Village: The Innovation of Tourism And Smes Activities for The Economic Independence of Trimurti Sub-Distric Comunity. Community service activities in the Trimurti Village focus on the Development of Tourism and SMEs. It was carried out using the Participatory Action Research (PAR) model, and it was then elaborated into several stages; situation analysis, partner group mapping, priority issue focus-based program, the application of solution resulting from the research, socialization, program implementation, supervision, monitoring, and evaluation. This activity aims to increase the economic independence of the people of Trimurti village as some weaknesses in terms of tour package making, product packaging, and digital social media-based marketing, which should be considered adequate as a marketing medium to attract the youth tourism market, can still be found. Tourism and SMEs' product packaging skill that can be considered lacking, including digital marketing, has made this village's potential less competitive in marketing compared to other districts in Bantul and DIY regions. The forms of activity programs that have been implemented during community service activities in Trimurti Village include (1) the Development of story comics guiding tours for Tourism Villages, (2) technical supervision for tourism village guiding, (3) preparation and calculation Training for tour package price rates for tourism villages (4) Implementation of the use of digital technology for tourism villages and tour packages sales (5) SMEs product photo training (6) Photography and digital content training for SMEs products (7) SMEs product designing and packaging training (8) SMEs product branding training (9) Social media management training for SMEs products selling accounts (10) SMEs product selling on the marketplace training (11) QRIS implementation as a marketplace payment method (12) Managing the legality of SMEs businesses.